Rh(III)‐Catalyzed Selective C8−H Acylmethylation of Quinoline N‐Oxides. Issue 21 (13th September 2018) - You, Chang; Pi, Chao; Wu, Yangjie; Cui, Xiuling
Abstract: A highly efficient Rh‐catalyzed regioselective C8−H acylmethylation of quinoline N‐ oxides with sulfoxonium ylides using N‐ oxide as the directing group under air atmosphere has been developed. This transformation has the generality of a broad scope of substrates, avoids external oxidants, and provides an efficient protocol to C8−H acylmethylated quinolines. Abstract :